Endovascular aortic repair with EndoAnchors demonstrate good mid-term outcomes in physician-initiated multicenter analysis—The PERU registry. (February 2022) - Reyes Valdivia, Andrés; Chaudhuri, Arindam; Milner, Ross; Pratesi, Giovanni; Reijnen, Michel MPJ; Tinelli, Giovanni; Schuurmann, Richte; Barbante, Matteo; Babrowski, Trissa A; Pitoulias, Georgios; Tshomba, Yamume; Gandarias, Claudio; et al.
Objectives: We aim to describe real-world outcomes from multicenter data about the efficacy of adjunct Heli-FX EndoAnchor usage in preventing or repairing failures during infrarenal endovascular aneurysm repair (EVAR), so-called EndoSutured-aneurysm-repair (ESAR). Methods: The current study has been assigned an identifier (NCT04100499) at the US National Library of Medicine (https://ClinicalTrials.gov ). It is an observational retrospective study of prospectively collected data from seven vascular surgery departments between June 2010 and December 2019. Patients included in the ANCHOR registry were excluded from this analysis. The decision for the use of EndoAnchors was made by the treating surgeon or multidisciplinary aortic committee according to each center's practice. Follow-up imaging was scheduled according to each center's protocol, which necessarily included either abdominal ultrasound or radiography or computed tomographic scan imaging. The main outcomes analyzed were technical success, freedom from type Ia endoleaks (IaEL), all-cause and aneurysm-related mortality, and sac variation and trends evaluated for those with at least six months imaging follow-up. Results: Two hundred and seventy-five patients underwent ESAR in participating centers during the study period. After exclusions, 221 patients (184 males, 37 females, mean age 75 ± 8.3 years) were finally included for analysis. Median follow-up for the cohort was 27 (interquartile range 12–48) months. A median 6 (interquartile range 3) EndoAnchors were deployed at ESAR, 175 (79%) procedures were primary and 46 (21%) revision cases, 40 associated with type IaEL. Technical success at operation (initial), 30-day, and overall success were 89, 95.5, and 96.8%, respectively; the 30-day success was higher due to those with subsequent spontaneous proximal endoleak seal. At two years, freedom from type IaEL was 94% for the whole series; 96% and 86% for the primary and revision groups, respectively; whereas freedom from all-cause mortality, aneurysm-related mortality, and reintervention was 89%, 98%, and 87%, respectively. Sac evolution pre-ESAR was 66 ± 15.1 vs. post ESAR 61 ± 17.5 (p < 0.001) and for 180 patients with at least six-month follow-up, 92.2% of them being in a stable (51%) or regression (41%) situation. Conclusions: This real-world registry demonstrates that adjunct EndoAnchor usage at EVAR achieves high rates of freedom from type IaEL at mid-term including in a high number of patients with hostile neck anatomy, with positive trends in sac-size evolution. Further data with longer follow-up may help to establish EndoAnchor usage as a routine adjunct to EVAR, especially in hostile necks.